Marketing Strategies of Public Sector Commercial Banks In India: Enhancing Competitiveness through Marketing Strategies (Journal of Advances and Scholarly Researches in Allied Education, 2011)
It  is  a must  for  the Public Sector  commercial  banks  to  introduce  marketing strategies if they want toparticipate in the international competition and improve their competitiveness.First of all, the SOCBs should be well aware of the international trends, takedetailed strategic goals into consideration and set their marketing targets.Second, the PSCBs should formulate relevant marketing strategies. Investigationand research is a priority. Meanwhile customers’ database should be established,which will help pave the way for the classification of markets. Third, thePSCBs should set up special program groups who will be responsible for theapplication of the marketing plans.